Aspek Hukum Tanggung Gugat Profesi Penunjang dalam Prospektus dan Perlindungan Hukum Bagi Investor yang Dirugikan dalam Rangka Pelaksanaan Prinsip Keterbukaan di Pasar Modal - Yudhi Setiawan (Fakultas Hukum Universitas Mataram, 2012)
Capital markets have a strategic role in national development as a source of long term financing for businesses who also is one investment alternative container for the owners of capital (investors) that tends to channel these funds into the banking and property sectors. The capital market is one of the collector container investors, who also is a provider of container funds (capital) for the community, which will use the funds for improvement and development of its business for the long term.